Gender inequality and cultural values in explaining gender differences in positive and negative emotions: A comparison of 24 countries during the COVID-19 pandemic - Robin Wollast (8344017) (2025)
The coronavirus pandemic posed a major challenge to mental health. Existing evidence shows that COVID-19 is related to poor emotional well-being, particularly among women. However, most work on the subject uses single-country samples, limiting the ability to generalize the disparity or explain it as a function of societal variables. The present study investigates the expression of positive and negative emotions during the pandemic as a function of gender and across 24 countries (N = 49,637). Strong gender differences emerged across countries, with women reporting more negative emotions (anxious, depressed, nervous, exhausted) and less positive emotions (calm, content, relaxed, energetic) than men. The gender gap in positive emotions was significantly wider in countries higher in individualism and narrower in countries higher in power distance. For instance, differences in emotions were larger in Western countries high in individualism, such as the USA, the UK, Italy, and France, and smaller in countries with higher collectivism and power distance, such as China, Malaysia, and South Korea, with a few exceptions like Japan and Brazil. These gender differences across countries were not explained by country-level gender inequalities indicators (GGGI and GII). Interestingly, the national severity of the pandemic, an epidemiological factor, reduced gender differences in positive emotions. These results underscore the importance of considering cultural and national factors when assessing gender differences in well-being. Other Information Published in: Current Psychology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12144-024-06989-0